POLITIK SELEBRITAS ELABORASI TEORITIK TERHADAP MODEL KAMPANYE BARU - Wasisto Raharjo Jati (Universitas Gadjah Mada, 2014)
The discussion about concept of celebrity politics is a new study in the social sciences and politicallandscape in the new Indonesian electoral democracy post-1999. Phenomenon of celebrity into therealm of practical politics itself actually comes as a vote getter nature every political campaign. Theexistence of massive publicity in the media as well as a performance appears to attract public sympathy.However, the pattern of these celebrities also performed by politicians to show any aspect of theirdaily life to become material for public consumption. The implication is that creating any sympathyand empathy from the public to candidate or party. Political journalism plays a major role in creatingboth the presence of the news by creating better and vice versa, creating a presence of construction tocandidates or parties. This paper will elaborate more on this celebrity political perspective.